The desire of "the other" arts in Antonio Carvajal’s poetry. The colaboration between artists - Sánchez-Mesa Martínez, Domingo (Tropelías: Review of Literary Theory and Comparative Literature, 2021)
The work of Antonio Carvajal (Albolote, Granada 1945) is highly representative of intermediality within the end of the XXth century poetry. There is an early conscious and voluntary quest in Carvajal’s poetry towards a dialogue with painting and music, mainly based in some certainty about the intermedial dynamics of the same poetic event. Beyond its classical and baroque roots, the poetics of Carvajal inherits the Baudelairian correspondence between the arts, thus a symbolist stance. Through a fruitful reading of Paul Valéry, with whom Carvajal shares a well appreciated vocation towards the ideology of music and the mastery of technical aspects in poetry writing, this writing aims to a renewed practice of pure poetry on the basis of poetry itself as common denominator of the arts. Since his most clearly interartistic book (anthology) Raso, Milena y Perla (1996), to some of his many and varied ways of collaboration and interchange with painters, as it is the case of the livre d’artiste El deseo es un agua (1998), with serigraphies by Antonio Jiménez, this article drives to classify and elucidate these various strategies and meanings of the intermedial dialogue practiced by Antonio Carvajal.